The Effect Of Ethanol–Pertamax Fuel Blends On Corrosion Rate And Visual Characteristics Of Fuel Tank - Naufal Hanif Musyaffa; Setya Wijayanta; Femmy Sofie Schouten (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2025)
Previous studies on ethanol fuel blends have mainly focused on corrosion rate using weight loss methods, simplified specimens, and limited fuel variations. However, visual characteristics under real fuel tank conditions remains less explored. To address this gap, this study examines the effect of ethanol concentration in pertamax fuel on the corrosion rate and visual characteristics of motorcycle fuel tank materials. Specimens from a 155 cc automatic motorcycle fuel tank were immersed in ethanol–pertamax blends with ethanol concentrations of 0%, 5%, 10%, 15%, 25%, and 85% for 12 weeks. A combined approach using the weight loss method and ImageJ based image processing was applied to obtain a more comprehensive evaluation of corrosion rate and visual characteristics. The results show that the highest corrosion rate occurred at PXE 25 with 0.057 mm/y, while the lowest was observed at PXE 0 with 0.007 mm/y. At PXE 85, the corrosion rate decreased to 0.038 mm/y, indicating a shift in corrosion behavior at higher ethanol concentrations. Image analysis confirmed that the largest corrosion area also occurred at PXE 25. These findings indicate that ethanol concentration affects corrosion characteristics, with different corrosion responses observed at higher ethanol blends, highlighting key implications for material selection, fuel system design, and ethanol fuel policy evaluation in Indonesia.